SECONDARY SCHOOL STUDENTS’ ERROR OF TERM OF ALGEBRAIC FORMS BASED ON MATHEMATICAL COMMUNICATION - Cholily, Yus Mochamad; Kamil, Tika Rifky; Kusgiarohmah, Putri Ayu (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this study is to describe students’ error on (1) the ability to understand the term of algebraic forms, and (2) the ability to communicate the term of algebraic forms into words and verbal forms. This is a case study. The study shows that: (1) the ability to understand the term of algebraic forms are low because of misunderstanding the slight differences between exponent and algebra itself, and (2) the ability to communicate the term of algebraic forms into words and verbal forms are challenging for them especially when they do not really understand the concepts.